Conservation and diversity of the IrrE/DdrO‐controlled radiation response in radiation‐resistant Deinococcus bacteria. Issue 4 (11th April 2017) - Blanchard, Laurence; Guérin, Philippe; Roche, David; Cruveiller, Stéphane; Pignol, David; Vallenet, David; Armengaud, Jean; de Groot, Arjan
Abstract: The extreme radiation resistance of Deinococcus bacteria requires the radiation‐stimulated cleavage of protein DdrO by a specific metalloprotease called IrrE. DdrO is the repressor of a predicted radiation/desiccation response (RDR) regulon, composed of radiation‐induced genes having a conserved DNA motif (RDRM) in their promoter regions. Here, we showed that addition of zinc ions to purified apo‐IrrE, and short exposure of Deinococcus cells to zinc ions, resulted in cleavage of DdrO in vitro and in vivo, respectively. Binding of IrrE to RDRM‐containing DNA or interaction of IrrE with DNA‐bound DdrO was not observed. The data are in line with IrrE being a zinc peptidase, and indicate that increased zinc availability, caused by oxidative stress, triggers the in vivo cleavage of DdrO unbound to DNA. Transcriptomics and proteomics of Deinococcus deserti confirmed the IrrE‐dependent regulation of predicted RDR regulon genes and also revealed additional members of this regulon. Comparative analysis showed that the RDR regulon is largely well conserved in Deinococcus species, but also showed diversity in the regulon composition. Notably, several RDR genes with an important role in radiation resistance in Deinococcus radiodurans, for example pprA, are not conserved in some other radiation‐resistant Deinococcus species. Abstract : The cleavage of repressor protein DdrO by metalloprotease IrrE results in induced transcription of the radiation response regulon in radiation‐resistant Deinococcus bacteria. DdrO cleavage by IrrE is stimulated by zinc ions. Among different Deinococcus species, there is diversity in the genes belonging to the regulon.